Annotated checklist of the bat flies (Diptera: Nycteribiidae) of Romania - Péter, Áron; Mihalca, Andrei Daniel; Sándor, Attila D. (Zootaxa, 2022)
Bat flies (Diptera: Hippoboscoidea: Nycteribiidae, Streblidae) are obligate, blood-feeding, highly specialized ectoparasites of bats (Chiroptera). Of the 17 nycteribiid species present in Europe, 11 have been recorded in Romania. Here, we present a checklist with all the previously published data and new records from recent years, for a total of 2218 records of bat-bat fly associations. Host-parasite associations are updated for Basilia italica Theodor, B. nana Theodor, B. nattererii (Kolenati), Nycteribia kolenatii Theodor & Moscona, N. latreillii (Leach), N. pedicularia Latreille, N. schmidlii Schiner, N. vexata Westwood, Penicillidia conspicua Speiser, Pe. dufourii (Westwood) and Phthiridium biarticulatum Hermann.